Engaging a disadvantaged community with a fruit and vegetable box scheme. (25th January 2018) - Zorbas, Christina; McCartan, Julia; De Mel, Randini; Narendra, Karthika; Tassone, Eliza C.; Yin, Ebony; Palermo, Claire
Abstract: Issue addressed: Interventions which target the determinants of unhealthy diets are required to promote healthy eating and reduce the burdens of diet‐related diseases such as cardiovascular disease, diabetes and some cancers. Methods: Qualitative interviews (n = 12) were conducted to explore the perspectives and experiences of local stakeholders regarding the implementation and uptake of a healthy eating initiative (a fruit and vegetable box scheme) in a disadvantaged, regional community. Results: Factors affecting the community's engagement included marketing strategies, customer experiences, a community‐centred approach, partnerships and logistics. Conclusions: Community engagement is often essential for an intervention to be effective. The factors which influence community engagement should be considered during planning, especially when targeting disadvantaged groups. So what?: Behavioural change interventions may continue to be met with limited success if community engagement and the overarching structural barriers to healthy eating are not addressed.